Vegetal ornaments in the Late Avar decorative art - Szenthe, Gergely (Dissertationes Archaeologicae, 2013)
Abstract of PhD thesis submitted in 2013 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Tivadar Vida. This paper is the modified version of the abstract of my doctoral thesis. The thesis discusses the vegetal ornaments of the Late Avar period (ca. a long 8th century AD) from the perspective of the cultural history, with the aim to create a basis for social historical studies. The Late Avar period had an art of ornamental functions. According to their inner structure the four different ornamental phases of the Late Avar period may have been determined by external cultural trends mostly of the Mediterranean. As the substance of the Mediterranean ‘dark age’ was regionalisation, the Late Avar material culture showed some autonomous features. The global cultural processes based on the social transformation of the Late Antique Mediterranean and Western-European world led to different cultural phenomena under the different social circumstances of the Avar milieu.